Halal integrity inspector: a game-based learning approach to ensuring halal standards and compliance / Mohamad Idlan Nazmi Mohammad and Azlan Abdul Aziz - Mohammad, Mohamad Idlan Nazmi; Abdul Aziz, Azlan (College of Computing, Informatics, and Mathematics, 2024)
Project “Halal Integrity Inspector” used game-based learning to solve hurdles. The major difficulty is that non-Halal products repeatedly use the Halal logo without permission. This alarming ability makes Halal products unreliable, causing moral and religious issues. Complex Halal certification for many venues is routinely disregarded. This mechanism is poorly understood, exacerbating mislabeling. Halal Integrity Inspector addresses these issues. This amusing and useful puzzle game teaches people to spot bogus Halal products. Continuous development with agile approaches is more systematic. The agile phases of Planning, Design, Development, Testing, Deploy, and Review enhance development. Final assessment of user engagement using Competence, Immersion, Flow, Tension, Challenge, Negative Affect, and Positive Affect. Total involvement was 68.23%, encouraging. Immersion (88.14%) and Positive Affect (88.69%) showed good connections. Challenge, tension, and negative affect were suggested improvements. This study found that user feedback improves game design and immersion. This project concludes with future work proposals. This project can expand with VR/AR. This tool helps Halal industry navigation. AI is a fast-growing technology that should be used and trained.